'Does the mirror speak my language?' A Comparison of L1 and L2 Student Reflections on Their Experiences in a Small-group Writing Tutorial. (August 2016) - Kelly, Lauren J.
Reflection has often been considered a powerful tool for students in composition, helping them develop rhetorical awareness and the ability to transfer their knowledge to future writing tasks. However, the methods that promote reflection have often been debated, and students have considered the process both puzzling and difficult. Furthermore, few studies have directly compared the reflections of native (L1) and non-native (L2) speakers to determine if they are likely to reflect in the same ways and if methods to improve reflective writing would be effective for both groups. To assist in this endeavour, the current study builds on work by Krol (1996) and Kathpalia and Heah (2008) to categorize student reflections and the developments they select to discuss in the small-group tutorial program for L1 and L2 speakers at a large, research university. The aim of this work is to better understand how and to what extent these students are reflecting to help guide the program and offer suggestions that could be more widely applied to peer review groups and composition classrooms in general. This study also indicates future areas of inquiry, including analysing how the number of guiding questions provided influences reflection, assessing student reflections before and after modelling, and comparing the reflections of L2 students with different native languages.